ISLAMIC LAW PERSPECTIVE ON INVESTMENT - Dwi Amanda Simanjuntak; Kenanga Safitri; Dwi Rani Rahayu; Natasya Salsabila Nainggolan; Rizqa Amelia (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
This research aims to explain the perspective of Islamic law on investment. Investment is an activity carried out by individuals or institutions with the aim of obtaining financial benefits in the future. In the Islamic context, investments must adhere to the principles of Sharia law, which govern justice, halalness, and blessings. This article outlines the concepts and principles of investment in Islamic law, including the prohibitions against riba (usury), gharar (uncertainty), and maysir (gambling). Additionally, it discusses the types of investments permitted in Islam, such as mudharabah (profit-sharing partnership), musyarakah (capital partnership), and ijara (lease). Furthermore, it highlights the importance of ethics and social responsibility in investment based on Islamic values. The results of this study show that the Islamic legal perspective on investment has unique principles and provides guidance for Muslims in managing their finances with regard to moral and ethical aspects. This research is expected to provide better insights into investments that are in accordance with Islamic principles and can serve as a reference for interested individuals or institutions seeking to make investments based on Islamic values.